Seasonal Variation in Terrestrial Invertebrate Subsidies to Tropical Streams and Implications for the Feeding Ecology of Hart’s Rivulus (Anablepsoides hartii) - Owens, David C.; Heatherly, Thomas N.; Eskridge, Kent M.; Baxter, Colden V.; Thomas, Steven A. (Frontiers in Ecology and Evolution, 2022)
Terrestrial invertebrates are important subsidies to fish diets, though their seasonal dynamics and importance to tropical stream consumers are particularly understudied. In this year-round study of terrestrial invertebrate input to two Trinidadian headwater streams with different forest canopy densities, we sought to measure the mass and composition of terrestrial inputs with fall-in traps to evaluate the influences of seasonality, canopy cover, and rainfall intensity, and; compare terrestrial and benthic prey importance to Anablepsoides hartii (Hart’s Rivulus), the dominant invertivorous fish in these streams, by measuring benthic and drifting invertebrate standing stocks and the volume and composition of invertebrates in Rivulus guts throughout the year. The biomass of terrestrial invertebrate fall-in was 53% higher in the wet versus dry season; in particular, ant input was 320% higher. Ant biomass fall-in increased with the density of canopy cover among sampling locations within both streams. Greater precipitation correlated with increased ant inputs to the more open-canopied stream and increased inputs of winged insects in the more closed canopy stream. The biomass of benthic invertebrates was reduced by more than half in the wet season in both streams. We detected no differences in the total volume of terrestrial prey in Rivulus diets between seasons, though ants were a greater proportion of their diet in the wet season. In contrast, benthic prey were nearly absent from Rivulus diets in the wet season in both streams. We conclude that terrestrial invertebrates are a substantial year-round prey subsidy for invertivores in tropical stream ecosystems like those we studied, which may contrast to most temperate streams where such terrestrial inputs are significantly reduced in the cold season. Interestingly, the strongest seasonal pattern in these tropical streams was observed in benthic invertebrate biomass which was greatly reduced and almost absent from Rivulus diets during the wet season. This pattern is essentially the inverse of the pattern observed in many temperate streams and highlights the need for additional studies in tropical ecosystems to better understand how spatial and temporal variation in terrestrial subsidies and benthic prey populations combine to influence consumer diets and the structure of tropical stream food webs.